Genetic Divergence of the Rhesus Macaque Major Histocompatibility Complex - Daza-Vamenta, Riza; Glusman, Gustavo; Rowen, Lee; Guthrie, Brandon; Geraghty, Daniel E. (Genome Research, 2004)
The major histocompatibility complex (MHC) is comprised of the class I, class II, and class III regions, including the MHC class I and class II genes that play a primary role in the immune response and serve as an important model in studies of primate evolution. Although nonhuman primates contribute significantly to comparative human studies, relatively little is known about the genetic diversity and genomics underlying nonhuman primate immunity. To address this issue, we sequenced a complete rhesus macaque MHC spanning over 5.3 Mb, and obtained an additional 2.3 Mb from a second haplotype, including class II and portions of class I and class III. A major expansion of from six class I genes in humans to as many as 22 active MHC class I genes in rhesus and levels of sequence divergence some 10-fold higher than a similar human comparison were found, averaging from 2% to 6% throughout extended portions of class I and class II. These data pose new interpretations of the evolutionary constraints operating between MHC diversity and T-cell selection by contrasting with models predicting an optimal number of antigen presenting genes. For the clinical model, these data and derivative genetic tools can be implemented in ongoing genetic and disease studies that involve the rhesus macaque.
10.1101/gr.2134504